Analysis of factors influencing green environmental performance of hotels in West Sumatra - Andrefson, Edo; Yasri, Yasri; Evanita, S (International Journal of Innovative Research and Scientific Studies, 2025)
The hospitality industry in West Sumatra faces challenges in improving environmental performance due to the increasing number of tourists and the waste generated. This study aims to analyze the influence of green intellectual capital, green transformational leadership, and green human resource management on environmental performance through employees' pro-environmental behavior. A quantitative approach was employed using the Structural Equation Modeling (SEM)-PLS method, involving 536 respondents from 268 hotels in West Sumatra. The analysis results indicate that green intellectual capital directly affects environmental performance (p < 0.000) and pro-environmental behavior (p < 0.033). Green human resource management influences both environmental performance (p < 0.016) and pro-environmental behavior (p < 0.000). Green transformational leadership only affects pro-environmental behavior (p < 0.048) but does not significantly impact environmental performance (p < 0.766). An indirect effect was found in green intellectual capital on environmental performance through pro-environmental behavior (p < 0.009) and green human resource management (p < 0.029). Employees' pro-environmental behavior has been proven to be a mediating variable that strengthens the relationship between organizational factors and hotel environmental performance. This study emphasizes that investing in green intellectual capital and green human resource management strategies is essential to enhance the sustainability of the hospitality industry. The recommendations include strengthening green policies, providing continuous employee training, and offering incentives for hotels committed to sustainability.